The similia principle - Bellavite, Paulo; Lussignoli, Sabrina; Semizzi, Marlia Lucia; Ortolani, Riccardo; Signorini, Andrea (British Homeopathic Journal, 1997)
We have developed two models of the similarity principle, essentially based on the regulatory mechanisms of biological homeostasis. A first model (gating theory) is designed to explain a series of experimental findings obtained in our laboratory, pointing to the occurrence of inverse effects of various agents on human neutrophils in vitro. A second, more general, model (regulation of stressed homeostatic networks) is designed to integrate modern concepts of priming, desensitization and signal transduction into the classical homeopathic theory of inversion of effect at the clinical level, i.e. the symptom-based similia principle.
Keywords: Similia principle; Homeostasis; Leukocytes; Receptors; Transduction systems; Gating theory; Stress; Inverse effects; Hormesis.